PENGARUH MEDIA EXPOSURE, MANAJEMEN LABA, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Indra Sakti Muda Fahlevi (2022)
Abstract Disclosure of corporate social responsibility is still very little done by companies with all sectors in Indonesia. It was recorded that in 2018 through the data presented by the ASEAN CSR Network, Indonesia was in the last position of the 4 other ASEAN countries. This shows that companies in Indonesia still lack a sense of concern for environmental and social issues. This study is a quantitative study which aims to determine and analyze empirically the relationship between media exposure, earnings management, and company growth on corporate social responsibility disclosure. This study uses secondary data from mining companies listed on the Indonesia Stock Exchange from 2018 to 2020. The sampling criteria were taken using a purposive sampling technique with the acquisition of a sample of 102 observation samples. Hypothesis testing in this study uses multiple linear regression models. The model is processed using the help of Microsoft Excel and STATA applications. The results obtained from this study include that media exposure has a negative effect on the disclosure of corporate social responsibility. Earnings management has no effect on the disclosure of corporate social responsibility. The company's growth has no effect on the disclosure of corporate social responsibility. Keywords: disclosure of corporate social responsibility, media exposure, earnings management, company growth